POSITION OF A NOTARY PUBLIC IN INVESTIGATIONS RELATING TO ALLEGED VIOLATIONS - Silalahi, Wilma; Sudiro, Ahmad (DE LEGA LATA: JURNAL ILMU HUKUM, 2025)
A notarial deed is a perfect form of evidence and must therefore be prepared to serve as a strong evidentiary basis in the event of a breach of contract. Thus, a notary in carrying out his/her duties must act trustworthy, honest, thorough, independent, impartial, and safeguard the interests of the parties involved in legal actions. In fact, the notary's duty is basically to express the wishes or actions explained by various parties which will be included in the deed. Thus, the interesting problem in this study is how the notary's position in the investigation related to alleged violations. This study uses a normative legal approach or doctrinal research. For notaries suspected of committing violations in the investigation, the notary can be positioned as a witness or suspect or co-defendant, depending on the notary's involvement in the alleged violation. In the process of examining a notary, investigators are required to obtain approval from the Notary Honorary Council, both for examination as a witness and for confiscation of documents. Therefore, regarding the approval of the Notary Honorary Council, it is not intended to complicate the investigation process or the need for examination of the notary, because this has been anticipated by the provisions of Article 66 paragraph (3) and paragraph (4) of Law 2/2014. Where investigators can obtain an answer no later than 30 (thirty) days. Therefore, there are no issues related to the request for approval from the Notary Honorary Council. If the 30-day deadline is exceeded, the request is deemed approved